Optimasi CMC-Na dan Gliserin dalam Sediaan Gel Ekstrak Lidah Buaya secara Simplex Lattice Design - Martina Indah Anita; Agatha Budi Susiana lestari (JURNAL ILMU KEFARMASIAN INDONESIA, 2023)
Aloe vera (Aloe barbandesis Mill.) is a plant with many benefits, such as an antibacterial agent. A gel dosage form has many advantages, such as being easy to use, not sticky, and quickly washed with water. This pure experimental study aims to obtain the optimal composition of CMCNa as a gelling agent and glycerin as a humectant to produce a gel with good physical properties and physical stability using the Simplex Lattice Design. The results of the responses of spreadability, viscosity, viscosity shift, and spreadability shift were used to determine the optimum formula and were analyzed using Software Design Expert. The results of the research found that the optimum formulas were formulas 1, 2, and 3 with a concentration of CMC-Na and glycerin, respectively, which were 1.500 g and 1.750 g; 1.563 g and 1.688 g; and 1.625 g. In addition, formulas 1, 2, and 3 fulfill the gel's physical properties and stability parameters.